"A slow and unrewarding and miserable pause in your life": Waiting in medicalized gender transition. (November 2020) - Pitts-Taylor, Victoria
Waiting is a common experience in medicalized gender transition. In this article, I address subjective experiences of medicalized gender transition through a temporal lens, focusing on personal narratives of wait lists, setbacks, and other delays experienced by trans patients. I consider administered waiting as a biopolitical practice of governance, one that has subjectifying and somatic effects on individuals and that speaks to the role of time in the administration of bodies, sex/gender, and biomedical citizenship. I ground my discussion in narratives created by trans people that chronicle their gender transitions; I analyze a set of gender transition vlogs appearing on YouTube, focusing on temporal aspects of medicalized transition and experiences of waiting. My discussion recognizes that the temporal modes of gender transition are multivalent, but these social media narratives also suggest being made to wait is an experience of power relations, one that is capable of producing submission, weariness, and precarity.